The Determinants of Child Mortality Reduction in the Middle East and North Africa - Iqbal, Farrukh; Kiendrebeogo, Youssouf (Taylor and Francis, 2016)
Although child mortality rates have declined all across the developing world over the past 40 years, they have fallen the most in the Middle East and North Africa (MENA) region. We investigate the causes of this through an econometric model that differs from previous studies in using the change in child mortality, rather than its level, as the dependent variable. We show that the process of child mortality decline has been characterized by convergence, whereby countries with higher levels of initial child mortality have experienced faster declines than those with lower levels. In addition, we find that public spending on health, growth rates of income and levels of caloric adequacy are robust determinants of the change in child mortality over time. Neither initial mortality status nor caloric adequacy is likely to remain as important for the MENA region in the future as they have been in the past. The region has been benefitting less and less from the convergence momentum conferred by high initial child mortality as its mortality levels have declined over time and this will continue into the future. With regard to caloric adequacy, the region is unlikely to experience significant improvements in the future as it has already achieved a high level of food sufficiency. Accordingly, most countries in the region must look to achieving more rapid income growth and higher rates of appropriately targeted public spending on health in order to achieve further child mortality reductions in the future.